The design and construction of a tea molecular nitrogen laser system - Kurt, Adnan. (Thesis (M.S.)- Bogazici University. Institute for Graduate Studies in Science and Engineering, 1988., 1988)
In this study the design and construction of a molecular nitrogen laser intended as a pump source for a dye laser system is presented. This . laser radiation at a wavelength of 337.1 nanometers and uses Blumlein switching to achieve fast (N a few nanosecond width) and high peaK power (N a few hundred Kilowatts) pulses. It operates using atmospheric pressure nitrogen with a cavity length of ten centimeters. The incorporation of this laser into a wavelength tunable, pumped dye laser system is outlined. Methods for studying fast optical pulses are given. iv
Keywords: Lasers.; Lasers in chemistry.